The impact of dietary fatty acids on human adipose tissue. Issue 1 (24th February 2020) - Petrus, Paul; Arner, Peter
Abstract : Nutrition is a major variable factor in human environments. The composition of nutrients has changed markedly in recent decades which may contribute to the increased prevalence of metabolic diseases, such as obesity and type 2 diabetes. Fat is an important component of the diet which comes in various forms with fatty acids (FA) of different carbon chain lengths and saturation degrees. In addition to being an energy supply, FA function as potent signalling molecules and influence transcriptional activity. Among other tissues, dietary FA target white adipose tissue function, which is central in maintaining metabolic health. This review focuses on the possible role of dietary FA composition and its effect on human white adipose tissue expandability and transcriptional response. Altogether, the existing literature suggests that unsaturated fat has more benign effects on adipose tissue distribution when compared to long-chain saturated fat. However, the mechanisms of action remain poorly characterised.